Perencanaan Tempat Pengolahan Sampah (TPS) 3R di Kecamatan Panarukan Kabupaten Situbondo - Nugroho, Adelia; Novembrianto, Rizka (Faculty of Engineering, Universitas Serambi Mekkah, 2025)
The increasing population and rapid development in the Panarukan subdistrict of Situbondo regency have significantly impacted waste generation patterns, posing considerable challenges to waste management. This study proposes the construction of a 3R (Reduce, Reuse, Recycle) Waste Processing Station (TPS) as an alternative to the conventional collect-transport-dispose approach currently used in the area. The study uses primary data on waste generation and composition, measured and analysed according to the SNI 19-3964-1994 standard, as well as secondary population data from 2013 to 2023. A population projection was conducted using the geometric method with the lowest standard deviation (1.147) to predict future waste generation until 2033. The results showed that the sub-district produces 23,043 kg of waste per day, dominated by food waste (41.2%), plastic waste (23.9%) and paper/cardboard (17.3%). Projected waste production in 2033 is estimated to reach 25,046 kg/day (160.55 m³/day). The planned TPS 3R facility requires a total land area of 844.81 m² and has a processing capacity of 160.55 m³/day. Implementing TPS 3R is expected to reduce the volume of waste sent to landfills and support the national waste management target of reducing waste by 30% and handling 70% of it by 2025.